COVID-19 preventive behavior of the community in Southeast Sulawesi Province, Indonesia - Irnaningsih, Irnaningsih; Asriati, Asriati; Tosepu, Ramadhan (YCAB Publisher & IAKMI SULTRA, 2021)
Background: COVID-19 is the new infectious disease with mild to severe symptoms infecting thousands of people worldwide. Behavior is one factor affecting human health, whereas human behavior is strongly influenced by one's perception in conducting something and is related to knowledge, attitude, and action.Objective: This study aimed to analyze the effect of knowledge, attitudes, and actions toward COVID-19 prevention measures of the Konawe Regency community in Southeast Sulawesi Province, Indonesia.Methods: This is quantitative research in which the study was conducted using an analytical survey with a cross-sectional approach. The study was conducted from 29 December 2020 until 28 February 2021. Data were collected using a validated questionnaire and analyzed using binary logistic regression.Results: The finding suggested that the knowledge had not significantly influenced the COVID-19 prevention behavior of the community (p > 0.05). Meanwhile, attitude and action had a significant influence on COVID-19 prevention behavior (p < 0.05). The attitude was the most influential variable, with an EXP(B) value of 29.181 times, more likely causing the community not to comply with the COVID-19 health protocol. Conclusion: Attitudes and actions are important variables in understanding community behavior. This result can be a basis for increasing compliance towards COVID-19 prevention protocol in Indonesia and beyond.